2013
DOI: 10.1371/journal.pone.0073548
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeletal Protein RHAMM and ERK1/2 Activity Maintain the Pluripotency of Murine Embryonic Stem Cells

Abstract: Receptor for hyaluronan mediated motility (RHAMM, encoded by HMMR) may be a cell-surface receptor for hyaluronan that regulates embryonic stem cell pluripotency and differentiation, however, a precise mechanism for its action is not known. We examined murine embryonic stem cells with and without hemizygous genomic mutation of Hmmr/RHAMM, but we were not able to find RHAMM on the cell-surface. Rather, RHAMM localized to the microtubule cytoskeleton and along mitotic spindles. Genomic loss of Hmmr/RHAMM did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(51 reference statements)
2
17
0
Order By: Relevance
“…The phosphorylation levels of Erk1/2 and Akt were increased by CM treatment. Previous studies suggested that Erk1/2 serves as a key component in regulating the pluripotency of embryonic stem cells (Li et al, 2010;Jiang et al, 2013). In the present study, we showed that suppressing Erk1/2 decreases VEcadherin expression but rescues PPARγ expression.…”
Section: Discussionsupporting
confidence: 71%
“…The phosphorylation levels of Erk1/2 and Akt were increased by CM treatment. Previous studies suggested that Erk1/2 serves as a key component in regulating the pluripotency of embryonic stem cells (Li et al, 2010;Jiang et al, 2013). In the present study, we showed that suppressing Erk1/2 decreases VEcadherin expression but rescues PPARγ expression.…”
Section: Discussionsupporting
confidence: 71%
“…However, this MAP kinase plays complex roles in adipogenesis since sustained activity blocks adipocyte maturation and promotes insulin resistance [36, 37, 69, 70]. RHAMM expression has previously been reported to be high in dormant stem cells but is down-regulated during embryonic stem cell differentiation suggesting that lowering RHAMM levels, which affect ERK1,2 activity, may be an important step in initiating differentiation of a variety of stem cells [33, 71, 72]. Our results show that RHAMM function loss is a necessary and rather specific step in directing the differentiation of mesenchymal progenitors into mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most studied receptor proteins are CD44 and receptor for hyaluronan-mediated motility (RHAMM), as they participate in inflammation and cancer motility, migration and metastasis (Slevin et al, 2007; Lokeshwar et al, 2014; Tolg et al, 2014; Misra et al, 2015). Furthermore, both CD44 and RHAMM are associated with the development of stem cell and cancer stem cell (Jiang et al, 2013; Shigeishi et al, 2013; Kouvidi et al, 2014; Jordan et al, 2015). FAK/SRC-mediated ERK activation is involved in signaling event for stem cell development.…”
Section: Ha Receptors and Signalingmentioning
confidence: 99%